IMPLEMENTASI NILAI – NILAI PANCASILA DALAM MENGHINDARI ALIRAN SESAT DI KEHIDUPAN BERAGAMA MASYARAKAT INDONESIA - Hafni Fauziyyah; Dinie Anggraeni Dewi (JURNAL EDUKASI NONFORMAL, 2021)
This article has the purpose of exegeting and examining yaang's issues in society connected with the teachings of a cult connected with the implementation of niali - pancasila value. The scientific literature employs a qualitative approach study method. The discussion discussed a case of the alleged cult on banten as "hakekok balakasutak." It also talked about the characteristics of the cult, and how religion relates to pancasila. This is regarding pancasila on the first religious precepts. And pancasila is also an ideology of the country of Indonesia, which is known as an open ideology because it can adapt to the development of The Times and can communicate dynamically with the development of the environment